1966
DOI: 10.1161/01.cir.34.6.1081
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Assessment of Bundle-Branch Block

Abstract: Complete bundle-branch block was found in 57 of 1,560 (3.7%) electrocardiograms routinely recorded on members of a retirement community. Of this number, 19 were identified as left bundle-branch block (LBBB), while 38 fulfilled the criteria for right bundlebranch block (RBBB). Individuals with LBBB were found to have cardiomegaly more frequently than did individuals with normal electrocardiograms. Individuals with RBBB, regarded as a homogeneous group, also demonstrated a greater prevalence of cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 19 publications
1
9
1
Order By: Relevance
“…We found a 2-3 fold higher rate of age-adjusted bundle branch block patterns compared to the population studies which have reported rates of 2.4-5.1% in men over age 50 and 4.1% in men over 75 [17,[24][25][26][27]. This likely represents differences between the general population and those hospitalized with heart failure.…”
Section: Discussioncontrasting
confidence: 53%
“…We found a 2-3 fold higher rate of age-adjusted bundle branch block patterns compared to the population studies which have reported rates of 2.4-5.1% in men over age 50 and 4.1% in men over 75 [17,[24][25][26][27]. This likely represents differences between the general population and those hospitalized with heart failure.…”
Section: Discussioncontrasting
confidence: 53%
“…15 In a retirement community, a prevalence of bundle-branch block of 5.1% was found in the male population Ն52 years old. 12 The Tecumseh study showed the prevalence of bundle-branch block to be 2.4% in men Ͼ50 years old. 30 In the study by Kreger et al, 31 complete intraventricular block, defined as QRS Ն0.12 second, was strongly dependent on age, with a prevalence of 11% in men in the 8th and 9th decades, and was twice as common in men as in women.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of wide QRS has been investigated in several studies. 24,25 Among individuals with existing CHD, bundle-branch block has been shown as a significant independent predictor of mortality. 26 Other studies have found that individuals with bundle-branch block have no excess mortality.…”
Section: Discussionmentioning
confidence: 99%